A robótica educativa como recurso construcionista para o ensino de termologia - Foscarin Neto, Armando (2021)
The world is constantly changing, technology permeates the current society being more used in all its departments. Elementary students are indeed, “digitally born”, which means they have easy access to a serie of products which favour communication and the access to information. The new Base Nacional Comum Curricular (BNCC) takes into consideration this new reality, and when it proposes the fifth competence to be developed by the brazilian students it refers straight to this new reality stating that “understanding, using and creating digital technologies of information and communication in a critical, meaningful, reflexive and ethical way in several social practicals” (2019). We also reflected about the Teaching of Physics and its undeniable importance for the shaping of future citizens, to be well prepared and critical towards the reality they are inserted. Meeting the requirements from BNCC, the concepts of Thermology must be approached in the 7º grade of Elementary II, and being very abstract concepts and sometimes misinterpreting the cause of alternative conceptions, we thought about discussing these topics in our research. Another topic raised is the use of robotics as a didactic tool for teaching Physics content. To adapt to this requirement, our research sought to be as accessible as possible to the Brazilian reality, adopting free robotics to develop our activities. We then asked ourselves how we could propose an educational product that could encompass the theoretical premises of constructionism with Physics Education and educational robotics, based on the following research question: What is the potential of educational robotics as a constructionist resource for teaching of thermology? Our work sought to develop an alternative path for Physics Teaching, using a didactic sequence that supports its use in a Rover built following the precepts of educational robotics. The qualitative study was applied to teachers in the education network of the city of Passo Fundo. This conformation is due to factors external to the initial idea of this research, at the moment when the product would be applied, measures of social distance due to the covid-19 pandemic prevented it from being applied to students of the 7th year of the Elementary school in schools. Through analysis of recordings and the application of a form applied to the participants, this research pointed out that in fact the educational robotics used in a constructionist context can be used in the classroom in a meaningful way. The set of proposed activities brings a modern perspective to classic experimental activities developed in the classroom. The educational product originated in this dissertation is available at: <http://educapes.capes.gov.br/handle/capes/598448>.